Superior Mesenteric Artery Syndrome: A Classic Presentation of a Rare Entity - Tharu, Sunraj (Cureus, 2020)
A 32-year-old female with a past medical history of constipation (predominant irritable bowel syndrome (IBS) and gastro-esophageal reflux disease (GERD)) presented with a complaint of pain in the lower abdomen. She lost 20 pounds in three months with a current body mass index (BMI) of 19.5 kg/m2 (ref: normal level 18.5-24.9). Computed tomography (CT) of the abdomen with contrast showed very little intra-abdominal fat, enlarged proximal duodenum, and decreased aorto-mesenteric angle of 15.4(0) suggestive of superior mesenteric artery (SMA) syndrome. Per general surgery, the patient was managed conservatively: initially Nil Per Os (NPO), slowly transitioned to a clear liquid diet, soft diet, and solid diet. She tolerated the diet, improved clinically, and was discharged home.